ANALISIS PENGARUH BUDAYA ORGANISASI, MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL (Studi Pada Karyawan PT. Bank Rakyat Indonesia (Persero) Tbk Cabang Pemalang) - Saylendra Adityawan, 0935020509 (Students Journal of Economic and Management, 2017)
The research objective was to examine and analyze the influence of organizational culture, motivation and job satisfaction on organizational commitment of the employees of PT. Bank Rakyat Indonesia (Persero) Tbk Branch Pemalang.In this study population was all employees of PT. Bank Rakyat Indonesia (Persero) Tbk Branch Pemalang. The sampling technique used purposive sampling, the sampling technique to establish certain criteria in accordance with the purpose or problems studied. The criteria used for determining the sample is already working at least 3 years, age, education and reguler employee and contract jobs. Based on the calculation model of summary obtained magnitude adjusted R2 is 0.872 this means that 87.2% of the variation of organizational commitment can be explained by the variation of the three independent variables are the organizational culture, motivation and job satisfaction. Based on the results of multiple regression analysis showed that organizational culture has positive influence on organizational commitment. The effect was statistically significant on a smaller probability obtained Î± 5% (0.003